L’application des règles minima pour le traitement des détenus au Canada - Landreville, Pierre (Acta Criminologica, 1973)
AbstractENFORCEMENT OF THE STANDARD MINIMUM RULES FOR THE TREATMENT OF PRISONERS IN CANADAConditions inside prisons in Canada as elsewhere, have not been beyond reproach from the time detention was instituted as a type of punishment at the beginning of the nineteenth century.This is not surprising, for society took no further interest in a delinquent once he had been handed over to the penitentiary authorities. The Belgian penologist, Paul Cornil, pointed out the striking contrast that exists between the legal guarantees given an accused during his trial and the free hand given the penitentiary authorities when carrying out his punishment.But in 1955, at the First Congress of the United Nations for the Prevention of Crime and the Treatment of Delinquents, Standard Minimum Rules for the Treatment of Prisoners were adopted. In 1957, the Economic and Social Council approved these Standard Minimum Rules and asked the governments involved to approve their adoption and enforcement.A study of the legislation concerned with federal penitentiaries and Houses of Detention in the Province of Quebec, lead to the realization that the minimum rules for the treatment of prisoners are usually not protected by laws, regulations or by directives in these penal institutions. On the other hand, prison conditions are in fact consistent with the requirements of the rules. These conditions, however, are due to the good will of the authorities and cannot be controlled ; they are considered privileges rather than rights.As a result of these findings, we believe that the Standard Minimum Rules should be considered the Bill of Rights of all individuals deprived of liberty, convicted or not. To do this : 1) the guarantees provided by the Rules must be incorporated in Canadian law and in that of each province ;2) a thorough knowledge of the Rules must be given to the services, authorities and other groups involved, including the inmates and the public ;3) inmates must be given the means to have their rights respected by creating an organization that will control and enforce the Standard Minimum Rules ; 4) an evaluation must be made of the measures necessary for the enforcement of the Rules, the methods to be used and the results obtained.However, ideas on rights and privileges change quickly, especially in the field of corrections. Thus in 1972, the National Council on Crime and Delinquency published an Act to Provide for Minimum Standards for the Protection of Rights of Prisoners. This text is noteworthy because it rests on a principle which, in our opinion, should serve as a cornerstone for the re-evaluation of the rights of prisoners : « A prisoner retains all the rights of an ordinary citizen except those expressly or by necessary implication, taken from him by law. »Recognition of this kind would contribute towards alleviating the secondary effects of penal sentences, of imprisonment and public stigmatiza-tion.It would lead to a more humane, tolerant and responsible attitude towards those who are hardest hit by public censure.